Waist-to-height ratio assessment device - Ertie Abana; Mycah Accad; Marvin James Pagauisan; Patrick Taguiam; Mary Ronalie Ferrer (Institute of Advanced Engineering and Science, 2023)
Many diseases are associated with excess abdominal fat like cardiovascular diseases. Monitoring and controlling abdominal fat led to one of the many factors that can change the status of a person’s health. Awareness of the waist-to-height ratio (WHtR) can be a guide to adjusting to a person’s lifestyle and maintaining a normal WHtR value. This study developed the WHtR assessment device that automatically calculates the WHtR value, displays the health status, and suggests the ideal waist circumference. The device is composed of a microcontroller that interconnects the other components of the device. A touchscreen liquid crystal display component was used as an input and output unit at the same time. The several testing that was conducted revealed accurate WHtR value calculation. The device is effective in assessing the health status of all age groups. The ideal waist circumference from the device was compared to manual computation and found that the success rate is one hundred percent (100%).